A Study on Awareness and Willingness for Eye Donation Among Health Care Professionals in a Tertiary Care Teaching Hospital - Srinivasan Chinnasamy; Sumathi Periasamy; Vineetha Tupili; Fathima V A (National Board of Examinations Journal of Medical Sciences)
Background: According to WHO Globally at least 2.2 billion people have a near or distant vision impairment. In at least 1 billion or almost half of these cases, vision impairment could have been prevented or has yet to be addressed. Corneal opacity is the major cause of vision loss and blindness after Cataract and glaucoma. By donating eyes after death, a corneal blind person can see again through Corneal transplantation. The objective of the study is to assess medical, paramedical and allied health science students’ knowledge willingness and perceived obstacles regarding eye donation, aiming to raise awareness and underscore the significance of promoting the cause. Materials and Methods: This study is a cross sectional hospital based study conducted in Chengalpattu Medical college and hospital, Chengalpattu. The study population includes all the health care professionals. The total sample size calculated from the previous study was 400 based on a Venkatapathy Narendran et al. The study was conducted for a period of 6 months. A convenient sampling technique was used in our study. In this study we had included all the Doctors, Paramedical students, MBBS students, Post graduates, Nursing students in Chengalpattu medical college and hospital. Results: The majority of respondents (41.25%) are aged 20–30, with 65% being male. Students dominate the study (92%), mainly undergraduate medical (43.5%), while faculty represents only 8%. 73.75% knew eye donation is possible, and 77.5% were aware it occurs only after death. Consent awareness varied, with 87.25% believing friends could consent, while only 15.5% thought children could. Eligibility perceptions differed, with 60.5% considering diabetics eligible, 44.5% believing those with glasses could donate, and 72.5% recognizing the need for HIV/hepatitis screening. Conclusion: The study found that 56.75% were willing to donate eyes, 35.75% were not, and 7.5% had already pledged. While 84.9% knew corneas restore vision, 78.3% cited family objections as a major barrier.